Understanding the Cognitive Immersion of Hospitality Architecture in Culture and Nature: Cultural Psychology and Neuroscience Views - Xie, Haihui; Chen, Qianhu; Nespoli, Chiara; Riso, Teresa (Frontiers in Psychology, 2022)
Hotel architectural design plays a critical role in the hospitality experiences of consumers, and it is important to consider that people may have different aesthetic cognitions toward the sensory properties of nature (i.e., the architecture of the hotel), such as its color and texture, as well as the landscape. While neuroaesthetics has emerged as a nascent field in hospitality research, few studies have investigated how nature reflects aesthetic experiences in the human brain. Moreover, the neuroaesthetic interpretation of architecture through the aesthetic triad is a novel interdisciplinary field. A field survey conducted at Amanfayun, a hotel in Hangzhou, China, in support of our propositions proves that sensory-motor, knowledge-meaning, and emotion valuation systems play key roles in appreciating architectural aesthetics. This study demonstrates that the evaluation of fluency, complexity, and naturalistic patterns of an architectural masterpiece is achieved through the sensory-motor systems. Our results also prove that familiarity, expectations, context, and cultural background directly affect the aesthetic knowledge of an individual and the meaning of architecture. Moreover, the interaction of sensory-motor and knowledge elements is uniformly moderated by the emotion valuation systems, resulting in a balanced appreciation of aesthetic architecture. Finally, the study reveals the central roles of culture and nature in cognitive rejuvenation.